Histiocytic Sarcoma Associated with Coombs Negative Acute Hemolytic Anemia: A Rare Presentation. (26th June 2016) - Batra, Sandeep; Martin, Stephen C.; Nassiri, Mehdi; Qureshi, Amna; Markel, Troy A.
Abstract : Histiocytic sarcoma (HS) rarely involves extranodal sites, such as the spleen. We report a unique pediatric case of massive splenomegaly and refractory Coombs negative hemolytic anemia (CNHA) secondary to HS. The CNHA resolved completely after an emergent splenectomy. Next generation sequencing (NGS) revealed novel ASXL1, PTPN11, KIT, and TP53 mutations, unmasking a clonal heterogeneity within the same neoplasm.